Omicron surge and the future of COVID-19 vaccinations (Faculty of Medicine Universitas Indonesia, 2022)
The global surge of Omicron has caused significant concern. Omicron has caused new wave of infections in nations with adequate vaccine coverage. Omicron has around 30 mutations that are similar to the previous variant of concerns, possibly decreasing vaccine effectiveness (VE). Hence, the emergence of Omicron is predicted to be a significant public health challenge and may alter the future of COVID-19 vaccinations. Furthermore, other issues may affect vaccine policy in the future such as the never-ending vaccine inequity, waning immunity of current COVID-19 vaccines, decreasing VE against new emerging strains, and new findings regarding hybrid immunity. This literature review aimed to explore the possible steps forward using the most updated knowledge on COVID-19 vaccines and Omicron.